Immunogenicity of cholera vaccination in children with inflammatory bowel disease - Łukasz Dembiński; Anna Stelmaszczyk-Emmel; Katarzyna Sznurkowska; Agnieszka Szlagatys-Sidorkiewicz; Andrzej Radzikowski; Aleksandra Banaszkiewicz (Taylor & Francis Group, 2021)
The cholera vaccine can protect patients with inflammatory bowel disease (IBD) against both cholera and travelers' diarrhea. However, both immunosuppressive treatment and IBD can affect its vaccine immunogenicity. The aim of this study was to assess the immunogenicity and safety of the cholera vaccine in children with IBD. Children older than 6 years with diagnosed IBD were enrolled in this multicenter study. All patients were administered two doses of the oral cholera vaccine (Dukoral®). Anti-cholera toxin B subunit IgA and IgG seroconversion rates were evaluated in a group with immunosuppressive (IS) treatment and a group without IS treatment (NIS). Immunogenicity was assessed in 70 children, 79% of whom received IS treatment. Post-vaccination seroconversion was displayed by 33% of children, for IgA, and 70% of children, for IgG. No statistically significant differences were found in the immune responses between the IS and NIS groups: 35% vs. 27% (p = .90), for IgA, and 68% vs. 80.0% (p = .16), for IgG, respectively. One case of IBD exacerbation after vaccination was reported. The oral cholera vaccine is safe. The immunogenicity of the oral cholera vaccine in children with IBD was lower than previously observed in healthy ones. The treatment type does not seem to affect the vaccine immunogenicity.